To move or not to move: Dispersal of Orius insidiosus in strawberry plants - Alonso, Mariangeles (2024)
Spatial and temporal distribution of food resources influences predatory insects' foraging and dispersal behavior. Orius insidiosus (Say) (Hemiptera: Anthocoridae) is a good biological control agent of western flower thrips (WFT), Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), in the strawberry crop and consumes two-spotted spider mite (TSSM), Tetranychus urticae Koch (Acari: Tetranychidae), and pollen as well. Augmentative biological control programs may fail if, following release, predators disperse from the crop. We studied the dispersal of O. insidiosus as a function of pollen availability, density of their main prey WFT, and the presence of the alternative prey TSSM, within and between strawberry plants. We found that O. insidiosus remained on the flowers during the 24 h of the assay. The dispersal of predators to a neighboring flower with thrips was approximately six times greater from a flower without pollen than from a flower with pollen. When TSSM was the only prey available, O. insidiosus colonized the leaves, and its dispersal within the plant was greater. At the plot scale, the predator dispersal from the release plant to other plants also depended on the presence of flowering plants and prey. Our results highlight the importance of flowering plants and pollen availability in enhancing the persistence of O. insidiosus in strawberry plants. Releases of this predator in the strawberry crop should be after the beginning of flowering, even at low WFT densities.